PRODUKTIVITAS KIAI DAN PENGEMBANGAN KURIKULUM MADRASAH DINIYAH - Iwan Kuswandi (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
This study described the implementation of curriculum in madrasa diniyah and the contribution of the kiai in curriculum development in madrasa diniyah takmiliyah. This study is a case study. Data was collected through observation, interview and documentation and analyzed using qualitative analysis. The findings showed that the implementation of the madrasa diniyah curriculum founded by kiai, using the book written by the kiai from the middle East, however there are those written by kiai from Indonesia, for example made by Kiai Bashori Alawi, Kiai Idris Jauhari, Kiai Jamaluddin Kafie and Kiai Marzuqi Ma’ruf.